Meta‐Holographic Displays: Stimuli‐Responsive Dynamic Metaholographic Displays with Designer Liquid Crystal Modulators (Adv. Mater. 50/2020). Issue 50 (15th December 2020) - Kim, Inki; Ansari, Muhammad Afnan; Mehmood, Muhammad Qasim; Kim, Won‐Sik; Jang, Jaehyuck; Zubair, Muhammad; Kim, Young‐Ki; Rho, Junsuk
Abstract : A touch‐responsive meta‐holographic display, which is promising for interactive holographic displays with touch sensing or motion recognition is presented by Young‐Ki Kim, Junsuk Rho, and co‐workers in article number 2004664 . According to an applied surface pressure with a gentle finger touch, the floating holographic images encoded in a metasurface can be switched in real‐time. The liquid‐crystal‐integrated metasurface devices can be further functionalized to sense programmed stimuli such as electric fields and temperature.